Early and intensive nutritional strategy combining parenteral and enteral feeding promotes neurodevelopment and growth at 18 months of corrected age and 3 years of age in extremely low birth weight infants. (September 2016) - Ohnishi, Satoshi; Ichiba, Hiroyuki; Tanaka, Yuko; Harada, Sayaka; Matsumura, Hisako; Kan, Ayako; Asada, Yuki; Shintaku, Haruo
Abstract: Aim: To evaluate whether aggressive nutrition can improve long-term neurodevelopmental outcomes and growth in extremely low birth weight (ELBW) infants born appropriate for gestational age (AGA). Methods: This single-center cohort study included 137 ELBW AGA infants born in two epochs. The first group received standard nutrition (SN; n  = 79) consisting of amino acids started at 0.5 g/kg/day on Day 4 of life and increased to 1.0 g/kg/day. The second aggressive nutrition (AN) group received amino acids started at 1.5–2.0 g/kg/day within 24 h of life and increased to 3.5 g/kg/day. Parenteral and enteral feedings were combined in both groups. Neurodevelopmental outcomes by the Kyoto Scale of Psychological Development and growth were followed up to 18 months of corrected age or 3 years of age and compared by univariate and multivariate analyses. Results: Baseline characteristics were similar between the two groups. At 3 years of age, AN children had a significantly greater mean value of head circumference, but not length or weight, than SN children (49.1 vs 48.0 cm, p  = 0.014). The cognitive-adaptive (C-A) score in the AN group was also significantly higher than that in the SN group (98.3 vs 91.9 at 18 months, p  = 0.039 and 89.5 vs 83.1 at 3 years, p  = 0.047). AN infants born ≥ 26 weeks of gestation were less likely to develop borderline disability in C-A, language-social and overall developmental scores compared to gestational age-matched SN infants. Conclusion: Parenteral and enteral AN after birth improved the long-term cognitive neurodevelopment in ELBW AGA infants, especially in those born ≥ 26 weeks of gestational age, however results need to be confirmed in a larger, multi-site randomized trial. Highlights: We evaluated whether early aggressive nutrition can improve long-term neurodevelopmental outcomes and growth in extremely low birth weight infants born at appropriate for gestational age. Early aggressive nutrition improved long-term cognitive neurodevelopment at 18 months of corrected Age and 3 Years of Age in extremely low birth weight infants at AGA, especially in those born ≥ 26 weeks of gestational age. Early aggressive nutrition promoted significantly greater head circumference at 3 Years of Age.